x(13+x)=0

Simple and best practice solution for x(13+x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(13+x)=0 equation:


Simplifying
x(13 + x) = 0
(13 * x + x * x) = 0
(13x + x2) = 0

Solving
13x + x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(13 + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(13 + x)' equal to zero and attempt to solve: Simplifying 13 + x = 0 Solving 13 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + x = 0 + -13 x = 0 + -13 Combine like terms: 0 + -13 = -13 x = -13 Simplifying x = -13

Solution

x = {0, -13}

See similar equations:

| (3-i)(x-iy)=3-11i | | x+y=1.70 | | 12(x-4)-8(2x-7)=3(x+5) | | 3+10x=0.5 | | 7(v-4)=3v-4 | | 11x-54-8x-12=7x+30-6x | | 5u-43=9(u-7) | | 2(u+7)=-2u+30 | | 1.1(-0.3w+10)=7.7 | | 3=3(v+5)+3v | | p=2(3)+2(4) | | -6x+4(x-8)=-24 | | -4(3y)-5+3(5y+5)= | | -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 | | 12/2=6/x | | -19-4+28-35=-6-2m-5+3m | | 8/9(b-1/4)=2/3 | | -5(-5z)=150 | | 4n+3=86 | | -p+5(3p-2)+4= | | (5)(-2)+(5)(-2)(-3)= | | 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 |

Equations solver categories